Model of students’ professional competence formation - Sabirova, R.; Zhanserikova, D.; Topanova, G.; Autalipova, U.; Aplashova, A. (International Journal of Innovative Technology and Exploring Engineering, 2019)
The paper is focused on the process of students’ professional competence formation. The major emphasis is on the competencies related to social and educational activities in the context of the commercialization of education. The authors’ biggest contribution is a specially designed model. It describes the formation of students’ professional competence in social and educational activities. Professional competencies of students are a qualitative integral manifestation of personal traits with a focus on social and educational activities. It includes a certain level of individual development and the mastering of special knowledge, skills, and abilities, as well as self-development that contribute to the successful implementation of professional activities in the context of the commercialization of education. The formation of professional competencies is presented as a focused, systematic process. There is much evidence that this process requires a systematic pedagogical, psychological, and special knowledge to develop skills and abilities in organizing and conducting social and pedagogical work. The content of this process is a complex activity targeting professionally significant qualities, the acquisition of systematized knowledge and skills in the field of social pedagogical activity. The results of the study are of much importance for practical use in the university. The proposed model allows identifying the levels of formation of students’ professional competencies.
Keywords: Formation; Model; Professional competence; Social and educational activities; Students; The commercialization of education